DAMPAK PERNIKAHAN DINI DALAM PERSPEKTIF HUKUM ISLAM, KESEHATAN DAN PSIKOLOGI - Alfadiansyah, Harun; NUR, A. TAUFIK (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2024)
According to Law Number 1 of 1974, marriage is a legal union between a man and a woman, with the aim of forming a happy and lasting family or household. Law Number 1 of 1974 Article 31 Paragraph 3 Marriage will make certain changes, one of which is the distribution of roles between husband and wife, in marriage the husband has the role of head of the family, and the wife has the role of housewife. Article 7 paragraph (1) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage (UU 16/2019) stipulates that marriage is only permitted if the male and female parties have reached the age of 19. This interactive dialogue was held to provide knowledge about the impact of early marriage in terms of religion, health and psychology in Arabika Village, West Sinjai District, Sinjai Regency. Early marriage in the perspective of Islamic law, health and psychology is carried out by counseling methods through interactive dialogue activities, seminar participants are given material for approximately one hour on the impact of early marriage presented by speakers from the Sinjai Religious Court, the Health Service and DP3AP2KB, after which the participants are given a session for questions and answers about the impact of early marriage on the community. Not only that, there was also a session for the village government to follow up on the increase in the number of early marriages in Arabica villages.Keywords: Early Marriage, Perspective, Islamic Law, Health, Psychology